Fourth-year medical students’ experiences of diagnostic consultations in a simulated primary care setting - Witheridge, Annamaria; Ferns, Gordon; Scott-Smith, Wesley (International Journal of Medical Education, 2019)
Objectives: The aim was to explore the experiences of fourth-year medical students of diagnostic consultations in a simulated primary care setting, in order to gain an insight into the suitability of such simulated consultations for assessing the diagnostic reasoning skills of medical students. Methods: This single-centre study employed a qualitative, cross-sectional design. Twelve fourth-year medical students volunteered to be filmed across 21 simulated, primary care consultations. The setting closely resembled OSCE stations, with a clinician present at each station monitoring the students’ performance using a station-checklist. Upon completion of each station, participants reflected on their experiences using video-stimulated recall. Interviews were transcribed and analysed using Interpretative Phenomenological Analysis. Results: The simulated scenarios were often perceived to have limited fidelity with predictable outcomes. At times, preoccupation with the assessment checklist meant that students were more likely to focus on asking questions than interpreting the information they were gaining. Some students felt scrutinized during the consultations, while others struggled to adapt to the time pressure. Overall, the artificial setting seemed to promote a reductionist diagnostic approach and an attitude of ‘ticking boxes’ rather than engaging in active diagnostic reasoning. Conclusions: The present findings call into question the assumption that observation-based assessment of the performance of medical students during simulated consultations can be reliably used to assess their diagnostic skills. Future studies need to explore how current assessment modalities could be better adapted to facilitate active engagement in diagnostic reasoning.
Keywords: Diagnostic reasoning; simulation; assessment; medical students; primary care